High-Accuracy Measurement of Three-Dimensional Inclinations of Power Transmission Towers Using Reconstruction Model of Stereo Images - Yashan Hu; Weizhou Xu; Zengjun An; Gaoxin Wang (Advances in Civil Engineering)
The traditional inclination measurement method usually measures one-dimensional or two-dimensional inclinations of power transmission towers. This research proposed a method, which is feasible to measure three-dimensional (3D) inclinations using the stereo images of power transmission towers. The main work of this method is the 3D reconstruction of power transmission tower model using stereo images and the calculation of 3D inclinations. As for the 3D reconstruction, a method of calculating the matching cost using a combination of multichannel red–green–blue stereo pairs and Sobel edge detection stereo pairs is proposed to obtain accurate matching cost, and a method of invalid disparity judgment is proposed to detect the invalid disparities in small closed areas; as for the calculation of 3D inclinations, a 3D inclination calculation method is put forward to measure 3D inclinations by rotation and translation of different 3D reconstruction models. The experiment shows that the 3D reconstruction quality is good and the results of the 3D inclinations are accurate, which is of great value in the static or dynamic measurement of 3D inclinations of power transmission towers.